Quantification de l’érosion hydrique en nappe dans la moyenne vallée de l’Oued Sarrath (Haut-Tell, Tunisie) - Chérifa Aissaoui; Abdelhamid Ben Ghazi (VertigO, 2023)
This study has shown the main results related to the modeling and mapping of sheet water erosion in the middle valley of Oued Sarrath by applying the revised version of the empirical model of Wischmeier and Smith 1978 (USLE). For the elaboration of mapping erosion, we called upon a meticulous examination of a set of parameters. These are, in particular, rainfall, soil structure and texture, slope, type of vegetation cover and anti-erosion techniques. The cross-study of these parameters allowed us to perform a detailed mapping of soil losses. This is a map that summarizes the spatial distribution of degrees of sensitivity to water erosion and determines the rate of soil loss. The results estimate that the average loss of soil related to sheet water erosion in the middle valley of Oued Sarrath is 23,72 t/ha/year, which exceeds the tolerable rates in similar environmental conditions. It emerges from the detailed analysis of the sensitivity to the water erosion map that the rates of soil loss are unequally distributed in the middle valley of Oued Sarrath. The soil loss values linked to sheet water erosion are very low at the lowlands level but can attain up to 458,945 t/ha/year at the sloping reliefs level, devoid of anti-erosion protection means.